Quantitative evaluation of human bone mesenchymal stem cells rescuing fulminant hepatic failure in pigs. Issue 5 (16th February 2016) - Shi, Dongyan; Zhang, Jianing; Zhou, Qian; Xin, Jiaojiao; Jiang, Jing; Jiang, Longyan; Wu, Tianzhou; Li, Jiang; Ding, Wenchao; Li, Jun; Sun, Suwan; Li, Jianzhou; et al.
Abstract : Objective: Stem cell transplantation provides a promising alternative for the treatment of fulminant hepatic failure (FHF). However, it lacks fundamental understanding of stem cells' activities. Our objective was to clarify stem cell-recipient interactions for overcoming barriers to clinical application. Design: We used an in-house large-animal (pig) model of FHF rescue by human bone marrow mesenchymal stem cells (hBMSCs) and profiled the cells' activities. The control and transplantation groups of pigs (n=15 per group) both received a D-galactosamine (D-Gal) injection (1.5 g/kg). The transplantation group received hBMSCs via intraportal vein infusion (3×10 6 cells/kg) immediately after D-Gal administration. The stem cell-recipient interactions were quantitatively evaluated by biochemical function, cytokine array, metabolite profiling, transcriptome sequencing and immunohistochemistry. Results: All pigs in the control group died within an average of 3.22 days, whereas 13/15 pigs in the transplantation group lived >14 days. The cytokine array and metabolite profiling analyses revealed that hBMSC transplantation suppressed D-Gal-induced life-threatening cytokine storms and stabilised FHF within 7 days, while human-derived hepatocytes constituted only ∼4.5% of the pig hepatocytes. The functional synergy analysis of the observed profile changes indicated that the implanted hBMSCs altered the pigs' cytokine responses to damage through paracrine effects. Delta-like ligand 4 was validated to assist liver restoration in both pig and rat FHF models. Conclusions: Our results delineated an integrated model of the multifaceted interactions between stem cells and recipients, which may open a new avenue to the discovery of single molecule-based therapeutics that simulate stem cell actions.